2022
DOI: 10.1093/jnen/nlac048
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cell Senescence: A New Therapeutic Target for the Acute Treatment of Ischemic Stroke

Abstract: Aging is a major risk factor for cerebral infarction. Since cellular senescence is intrinsic to aging, we postulated that stroke-induced cellular senescence might contribute to neural dysfunction. Adult male Wistar rats underwent 60-minute middle cerebral artery occlusion and were grouped according to 3 reperfusion times: 24 hours, 3, and 7 days. The major biomarkers of senescence: 1) accumulation of the lysosomal pigment, lipofuscin; 2) expression of the cell cycle arrest markers p21, p53, and p16INK4a; and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Similar increases in neuronal cathepsin D and lysosomal storage material have been observed in degenerated regions of brains from patients with Alzheimer’s disease (AD) [ 21 , 22 ], though these changes are closely associated with AD pathology [ 23 ]. Accumulation of lysosomal storage material has also been observed in models of stroke [ 9 ], excitotoxicity [ 48 ] and traumatic brain injury [ 45 , 47 , 70 ], perhaps indicating a general relationship with neuronal stress or death. In contrast, CatD levels increase in some models of injury and excitotoxicity [ 11 , 13 , 16 ], but decrease in models of hypoxia and stroke [ 61 ] and at early time points after traumatic brain injury [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar increases in neuronal cathepsin D and lysosomal storage material have been observed in degenerated regions of brains from patients with Alzheimer’s disease (AD) [ 21 , 22 ], though these changes are closely associated with AD pathology [ 23 ]. Accumulation of lysosomal storage material has also been observed in models of stroke [ 9 ], excitotoxicity [ 48 ] and traumatic brain injury [ 45 , 47 , 70 ], perhaps indicating a general relationship with neuronal stress or death. In contrast, CatD levels increase in some models of injury and excitotoxicity [ 11 , 13 , 16 ], but decrease in models of hypoxia and stroke [ 61 ] and at early time points after traumatic brain injury [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous neurological diseases, including neurodegenerative conditions like Alzheimer's disease, Parkinson's disease, and stroke, are linked to cellular senescence ( 35 ). Cellular senescence of the cells happens as AIS, which develops and progresses ( 36 ). AIS and neurological damage are impacted by the senescence-associated secretory phenotype (SASP) ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the kidney and heart, brain is also prone to suffer from I/R injury. A recent study also showed that neuron senescence served as a pathogenic mechanism for ischemic stroke-induced brain damage [ 99 , 100 ], which might result in glial scar and cerebral fibrosis [ 101 ].…”
Section: Cellular Senescence Is the Core Mechanism Of Transition From...mentioning
confidence: 99%
“…On the one hand, senescent neurons induced by stroke have a significant increase in the expression of SASP including IL6, TNFα, and CXCL1 [ 99 , 100 , 102 ], which induce cerebral inflammation microenvironment forming and extracellular matrix(ECM) deposition by a pericyte-dependent manner [ 101 ]. On the other hand, in the early stages of cerebral IR injury, glial cells especially astrocytes are activated by pro-inflammatory cytokines generated by senescent neurons [ 101 , 103 , 104 ].…”
Section: Cellular Senescence Is the Core Mechanism Of Transition From...mentioning
confidence: 99%